(untitled) (Faridpur Medical College Journal, 2015)
Rheumatic mitral stenosis is still a cardiac problem in developing countries. Reconstructive and replacement surgery of the diseased valves are often needed. Most of the studies on stenotic mitral valves are echocardiographic one. Morphometric measurements of the stenotic mitral valve and comparison with that in the normal mitral valve is done in this study. Thirty seven hearts of normal adult-male unclaimed dead-bodies from the mortuary of Forensic Medicine, Dhaka Medical College, Dhaka; and twelve surgically excised stenotic mitral valves of the adult-male cardiac patients from the National Institute of Cardiovascular Diseases, Dhaka, Bangladesh were studied in fresh condition. The detail morphometric findings were compared between two groups. Though the total annular circumference was similar in both groups, yet the effective orifice area reduced significantly in stenotic valves. The anterior leaflet-area was increased, but the posterior leaflet-area was decreased in the stenotic valves. The thickness of the stenotic leaflets and chordae tendineae were increased compared to that in normal valves. The knowledge of the pathological changes of the valves would help to understand the exact pathophysiological mechanisms involved in the cardiac valve diseases. Faridpur Med. Coll. J. 2014;9(1): 7-11